The background, realisation and achievements of the Vojvodina economic development program - Juhász, Bálint (Studia Mundi – Economica, 2020)
By economic development we mean conscious intervention that aims to influence the direction of economic processes and the extent of economic change. In 2016, the Hungarian Government launched an economic development program in order to strengthen Hungarian communities who are living beyond the borders of mother country in the Carpathian Basin. The Vojvodina Economic Development Program is currently the largest cross-border economic development program of Hungary, which is a pioneer in the implementation of foreign economic development programs and serves as a model for the implementation of similar foreign programs.